Brand Experience and Brand Loyalty Relationship: A Study Under Attribution Theory Perspective - Shely Rizki Hardiana; Muhamad Ridwan (Applied Information System and Management (AISM), 2026)
Research on coffee shop brand loyalty has largely focused on factors like self-congruity, brand equity, and brand trust, while the role of brand experience remains underexplored. Moreover, its link to multidimensional loyalty outcomes and attribution theory has received little attention, especially in emerging markets. This study investigates how brand experience influences brand loyalty dimensions—willingness to pay more (WTPM), word-of-mouth recommendations (WOM), and repurchase intention (RI)—within Indonesian coffee shop brands, using attribution theory to explain the mechanisms. A quantitative approach was used, with 246 Indonesian coffee shop consumers completing a questionnaire. To confirm the assumptions, we applied partial least squares structural equation modeling (PLS-SEM). The findings reveal that brand experience significantly enhances all three factors of brand loyalty: WTPM, WOM, and RI. The research provides a theoretical foundation for understanding how brand experience affects customer loyalty, suggesting future studies could explore similar relationships in other cultural and market contexts. For coffee shop owners, the findings emphasize the need to enhance brand experience through sensory, emotional, and intellectual engagements. Tailoring environments for intellectual activities can help differentiate brands in a competitive market. The study emphasizes how coffee shops serve as social and intellectual hubs. By fostering such environments, coffee shops can enhance their value, offering spaces for cognitive engagement and social interaction.